FRI0453 Patients with ankylosing spondylitis have elevated soluble biomarkers of cardiovascular disease compared to controls. (23rd January 2014) - Berg, I. J.; Semb, A. G.; van der Heijde, D.; Dagfinrud, H.; Kvien, T. K.; Seljeflot, I.; Aukrust, P.; Ueland, T.; Provan, S. A.
Abstract : Background: Patients with ankylosing spondylitis (AS) have higher risk of atherosclerotic cardiovascular disease (CVD) than the general population, but few have studied soluble biomarkers of CVD in AS. Asymmetric dimethylarginine (ADMA) and ratio of L-arginine/ADMA are markers of endothelial dysfunction where elevated ADMA and reduced L-arginine/ANDA indicates increased risk of CVD. Osteoprotegerin (OPG) is a marker and regulator of arterial calcification and a predictor of CVD and adverse outcome. N-terminal pro-natriuretic peptide (NT-pro-BNP) is a predictor of myocardial function and cardiac mortality. Objectives: To compare levels of ADMA, L-arginine/ADMA, OPG and NT-pro-BNP in AS patient and controls. Methods: A cross-sectional study of AS patient and controls. AS patients recruited from a hospital cohort of AS patients diagnosed according to the mod New York criteria, were stratified according to age gender and residential area. Controls were selected according to these criteria. Data collection took place 2008-2010. ADMA, L-arginine/ADMA and OPG were analyzed from frozen plasma samples. NT-pro-BNP was analyzed consecutively. Demographic data were analyzed using bivariate tests as appropriate using SPSS 20. Comparisons of the biomarkers between AS and controls were analyzed by linear regression models, adjusted for age and gender. OPG and NT-pro-BNP were log transformed to obtain normality. Results: 151 patients and 143 controls were in the original cohorts, but due to missing data 145 patients and 125 controls were analyzed in this study. Demographic data showed no differences in male gender (AS vs. controls) 60.7% vs. 69.0%, p= 0.91 or smoking habits 13.9% vs. 23.2%, p=0.44. The AS patients were younger than the controls, mean (SD) 49 (11) vs. 53 (11) years, p=0.003. Both ADMA and OPG were significantly elevated and L-arginine/ADMA significantly reduced in AS compared to controls after adjustments of the demographic variables (table ), but levels of NT-pro-BNP were similar. Conclusions: AS patients have elevated ADMA and OPG and reduced L-arginine/ADMA, supporting that AS patients are at higher risk of CVD than the general population. Further validation in longitudinal settings should be performed. Disclosure of Interest: None Declared